Frequência alélica da variante dmrt3 g.22999655c>a (equcab2.0) em asininos e muares com marcha batida ou picada - Herman, Mariana (2023)
The DMRT3:g.22999655C>A SNP influences the gait types of horses, and the wild-C and mutant-A alleles have been associated with batida and picada gaits, respectively. Donkeys and mules also have batida or picada gaits, and this study aimed to determine the allele frequency of the DMRT3 SNP in gaited donkeys and mules and to verify whether the genotype influences the type of gait in these animals. Thus, 159-mules and 203-donkeys were genotyped. Among the 159 mules assessed, 47% had a CC genotype, and 53% had a CA genotype. The CC genotype was predominant in the donkeys (97%). The AA genotype was not found in the mules or donkeys. The CC and CA genotypes were similarly distributed in the mule group with batida or picada gaits. The frequencies of the CC genotype in the donkeys were similar, regardless of whether the gait was batida or picada. However, the CA genotype was more frequent in donkeys with a picada gait than in those with a batida gait. The previous description of the three genotypes in Mangalarga and Campolina horses, which are the main breeds involved in the production of marching mules in Brazil, explains the higher percentage of CA mules and the very low presence of the mutated allele in donkeys, allowing us to speculate that the mutated allele was inherited from the mares used in the crosses with donkeys. In addition, these results suggest that the gait is not influenced by the aforementioned mutation and that other genes and polymorphisms may influence the trait in equids.